A Prototype Detector Array for Measurements in Laser Accelerated Charged Particle Beams. (December 2020) - Vasilache, Radu A.; Popovici, Maria–Ana; Straticiuc, Mihai; Matei, Consuela Elena; Stroe, Daniela; Crăciun, Liviu; Radu, Mihai; Maria Niță, Laura Ana
Abstract: In all the future applications of the laser accelerated beams (as generated in the ELI and CETAL projects) in-beam dose measurements will be needed. The gold standard in dose measurement remain the ion chambers, but for the beams we intend to measure they do present some limitations given be the large number of corrections to be applied in order to calculate a correct dose from the measured charge. The ELIDOSE project is addressing these problems by proposing an array detector that would allow the simultaneous measurement of the recombination and polarity corrections, as well as of the dose – the QUADRO-fm (Quad Detector for RecOmbination factor measurement). The prototype detector consists of 4 identical ion chambers mounted together in a PMMA frame and the project analyses its response to various charged particle beams and the reciprocal influences of the chambers on each other. This reciprocal influences of the four chambers have been studied in well characterised therapy electron beams and conclusions regarding further developments have been drawn. The paper presents the characterisation of the proton and electron beams used in the experiment, as well as the dose measurements in the 5 MeV electron beams generated by a Siemens radiotherapy LINAC and the comparison with the FLUKA based simulations.